SUDDEN CORONARY DEATH. ETIOLOGY AND EPIDEMIOLOGY OF THE SUDDEN CORONARY DEATH - Z. J. Narzilloeva (Western European Studies, 2024)
Sudden coronary death is death in the presence of witnesses, occurring instantly or within 6 hours, most often caused by ventricular fibrillation and having no signs allowing a diagnosis other than ischemic heart disease. Sudden death occupies a major place in the structure of death from cardiovascular diseases. In the vast majority of those who suddenly died, the cause of death was coronary heart disease (CHD), usually caused by the development of atherosclerosis of the coronary arteries. Therefore, many issues related to the problem of sudden death, especially issues of its primary prevention, should be considered in connection with the prevention of atherosclerosis in general
Keywords: ventricular; especially; primary prevention